Using the Quran and Nahjul-Balagha in English Scientific Articles Published by Iranian Universities of Medical Sciences -2014 - Aram Tirgar; Zahra Aghalari; Davood Farajzadeh Alan (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Background and Objective: The Quran Al-Karim is not a book in the field of medicine and public health; however, it contains many verses in relation to health and hygiene. It also explores the root of events relevant to health and disease. Nahjul-Balagha also contains brilliant clues of health and hygiene. Therefore, the present study was conducted with the aim of determining the degree to which these two guidebooks have been utilized in writing medical articles. Method: The current applied, cross-sectional investigation was conducted by citation analysis; that is, frequency counts were obtained of original English language scientific articles which were published by Iranian universities of medical sciences in 2014. Data was collected using a researcher-made check-list through the survey of all scientific articles and their references. Descriptive statistical indicators were used for data analysis. In this study, The ethical issues were all considered and the authors declared no conflict of interest. Results: Of 201,071 studied references from 6,907 published articles and in 696 English language scientific journals belonging to 31 Iranian universities of medical sciences, Quran Al-Karim had been cited 218 times (less than 1%). Also, none of the articles had used Nahjul-Balagha as a reference. The most frequently cited Surahs of the holy Quran in published articles were Al-Baqarah, An-Nisa, Al-Anaam, and Al-Isra, in that order. Conclusion: Although the findings have shown that the Quran was cited as a reference among published articles in the field of medical sciences, its utilization rate seems to be inadequate. For downloading the full-text of this article please click here.